Model Integrasi Penjadwalan Batch dan Penjadwalan Preventive Maintenance dengan Kriteria Minimisasi Biaya Simpan, Biaya Setup, Biaya Pm, serta Biaya Rework pada Mesin Stabil - Zahedi, Zahedi (Bina Nusantara University, 2014)
This study developed a model of batch scheduling involving the unavailability machine to minimize setup costs, cost of preventive maintenance and the cost of rework in a stable machine. This model is considered necessary in order to understand the effect of the unavailability machine for production runs and to understand the effect on the batch production schedule. The results of this study indicate that the first and last run will not give single batch. Given a hypothetical example of how the model and algorithm developed solve the problem instance.